"I spy, with my little sensor": fair data handling practices for robots between privacy, copyright and security. Issue 3 (3rd July 2017) - Schafer, Burkhard; Edwards, Lilian
ABSTRACT: The paper suggests an amendment to Principle 4 of ethical robot design, and a demand for "transparency by design". It argues that while misleading vulnerable users as to the nature of a robot is a serious ethical issue, other forms of intentionally deceptive or unintentionally misleading aspects of robotic design pose challenges that are on the one hand more universal and harmful in their application, on the other more difficult to address consistently through design choices. The focus will be on transparent design regarding the sensory capacities of robots. Intuitive, low-tech but highly efficient privacy preserving behaviour is regularly dependent on an accurate understanding of surveillance risks. Design choices that hide, camouflage or misrepresent these capacities can undermine these strategies. However, formulating an ethical principle of "sensor transparency" is not straightforward, as openness can also lead to greater vulnerability and with that security risks. We argue that the discussion on sensor transparency needs to be embedded in a broader discussion of "fair data handling principles" for robots that involve issues of privacy, but also intellectual property rights such as copyright.